Faktor Predisposisi yang Mempengaruhi Perilaku Hidup Bersih dan Sehat di Tempat Umum (Pasar Passi, Gogagoman) - Darmin Darmin; Sudirman Sudirman (Universitas Gorontalo, 2022)
The government has established a Clean and Healthy Lifestyle management. Currently, PHBS is still being studied because the community has not been able to fully integrate it. A healthy market strategy is a collaborative effort to create a clean and healthy market condition. The Passi market, Gogagoman District, still has many vendors that do not pay attention to the application of clean and healthy living practices, resulting in the lack of cleanliness and comfort in the market environment. The goal of this research is to discover the primary factors impacting the behavior of PHBS traders in the Passi market. This is a quantitative descriptive study using a cross-sectional design and an observational questionnaire. The population is 320 persons, and the sample size is 195 people, as estimated using the Krejcie-Morgan formula and probability sampling. The T-test analysis revealed that the knowledge variable for PHBS was 0,022 and the attitude variable for PHBS was 0,019, (0.05), with t values = 2,312 and 2,373, respectively. The F-test analysis revealed that the knowledge and attitude factors concerning PHBS were 0,003. The knowledge and attitudes of traders about PHBS have a significant effect on the level of PHBS implementation in the Passi market. Environmental aspects, waste management, and infrastructure are very important to pay attention to. It is hoped that there will be socialization and market monitoring related to the application of clean and healthy living behavior to ensure the cleanliness, comfort, and health of the market environment.